Efficacy and Safety of Acupuncture and or Moxibustion for Managing Primary Dysmenorrhea: A Systematic Review and Meta-Analysis. (September 2022) - Liu, Weiting; Wang, Carol Chunfeng; Lee, Khui Hung; Ma, Xiaopeng; Kang, Timothy Leen
Acupuncture and moxibustion have been accepted as add-on options for primary dysmenorrhea (PD); however, the clinical evidence is still inadequate. We searched AMED, CENTRAL, EMBASE, PubMed, Web of Science, CBM, CNKI, VIP, Wangfang database, ANZCTR, ClinicalTrials.gov, and the WHO ICTRP, from their inception to February 2021. The pooled analysis of 13 RCTs with 675 participants for VAS showed that acupuncture and moxibustion were more effective in managing PD than the control group with the MD of −1.93 (95% CI [−2.80, −1.06] and −2.67 (95% CI [−4.96, −0.38]). With the CMSS, seven studies with 487 participants showed that these modalities were more effective than the control group with the MD of −7.58 (95% CI [−10.97, −4.19]) and −3.78 (95% CI [−6.90, −0.66]). The findings indicated that acupuncture and moxibustion could relieve pain effectively and has fewer adverse events (AEs) in managing PD.